Solid Lipid Nanoparticles as an Innovative Lipidic Drug Delivery System - Waghmare, Suchita; Palekar, Rohini; Potey, Lata; Khedekar, Pramod; Sabale, Prafulla; Sabale, Vidya (Pharmaceutical Nanotechnology, 2025)
In order to overcome some of the drawbacks of traditional formulations, increasing emphasis has recently been paid to lipid-based drug delivery systems. Solid lipid nanoparticles (SLNs) are promising delivery methods, and they hold promise because of their simplicity in production, capacity to scale up, biocompatibility, and biodegradability of formulation components. Other benefits could be connected to a particular route of administration or the makeup of the ingredients being placed into these delivery systems. This article aims to review the significance of solid lipid nanocarriers, their benefits and drawbacks, as well as their types, compositions, methods of preparation, mechanisms of drug release, characterization, routes of administration, and applications in a variety of delivery systems with a focus on their efficacy.
Keywords: Nanoparticles